The Impact of the Church Council’s Role in Improving Christian Religious Education at the Ina Parari Kamis HKBP Petra Church in Pematangsiantar Category - Sunggul Pasaribu; Ester Sitorus (Jurnal Ilmu Sosial dan Humaniora, 2026)
The role and duty of the congregation is to educate and teach God's Word to the ministry category of Women Thursday Society (Ina Parari Kamis) at HKBP Petra Pematangsiantar so that the member of the society can grow in faith and be active in any worship. As the duty of the church's call to the community in terms of fellowship, witness and service, the Word of God says [1]: "Hearing and reading the Word of God is an important and main thing in the growth of a person's faith in God in Jesus Christ (Romans 10:17). Moreover, the aim of this research is to improve the teaching of Christian Religious Education [2] and active worship as a form of faith that grows and develops (Ephesians 4:16). This research uses a problem-solving methodology. It is necessary to briefly explain the definition of the empirical indicators of the independent variable (X) and the dependent variable (Y). This research does not always directly examine the entire population, but a sample that can be considered representative of the population. Therefore, the population in this research is the ministry category of Woman Thursday Society (Ina Parari Kamis) at HKBP Petra Pematangsiantar Church